Do increased drilling speed and depth affect bone viability at implant site? - Reza Tabrizi; Ali Dehghani Nazhvanai; Mohammad Mahdi Farahmand; Sara Yasour Pourali; Sepanta Hosseinpour (Wolters Kluwer Medknow Publications, 2017)
Background: The aim of this study was to assess the effect of increasing the drilling speed and depth during implant site preparation on bone viability. Materials and Methods: In this prospective cohort study, participants were divided into four groups based on the speed and depth of drilling at the first molar site in the mandible. Participants underwent drilling at Group 1: 1000 rpm and 10 mm depth, Group 2: 1500 rpm and 10 mm, Group 3: 1000 rpm and 13 mm, and Group 4: 1500 rpm and 13 mm. Obtained specimens were assessed histologically to the qualitative measurement of bone viability, and the percentage of vital bone were evaluated by histomorphometric analysis. ANOVA was used to compare age and the mean percentage of vital bone and Tukey's test as post hoc was applied for pairwise comparison of groups. Results: A total of 100 participants were studied in four groups (25 subjects in each group). Histological evaluation revealed a low level of bone viability maintenance in all groups. Histomorphometric analysis showed the mean percentage of vital bone was 9.5 ± 3.91% in Group 1, 8.86 ± 3.84% in Group 2, 8.32 ± 3.80% in Group 3, and 4.27 ± 3.22% in Group 4. A significant difference was noted in the mean percentage of bone viability among the four groups (P = 0.001). Conclusion: It seems that increasing the drilling speed or depth during dental implant site preparation does not affect the mean percentage of cell viability, while the increase in both depth and speed may decrease the percentage of viable cells.